Effect of Application of Sole Organic, Inorganic Fertilizers and their Combinations on the Growth and Biological Yield of Fluted Pumpkin (Telfairia occidentalis) (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
The effect of application of sole organic, inorganic fertilizers and their combinations was investigated on the growth and biological yield of Fluted pumpkin (Telfairia occidentalis) at the Teaching and Research Farm, Babcock University, Ilishan Remo, Ogun state, Nigeria. Ten treatments were involved namely: No fertilizer (control), 100kgN/ha as Sulphate of Ammonia, SA (21%N), 100kgN/ha as Composted Maize Cob, CMC (0.97%N), 100kgN/ha as Composted Saw Dust, CSD (1.01%N), 50:50 CMC/SA combination, 50:50 CSD/SA combination, 50:50 CMC/CSD combination, 75:25 CMC/SA combination, 75:25 CSD/SA combination, 75:25 CMC/CSD combination, the treatments were replicated four times using Randomized Complete Block Design (RCBD). Seedling emergence, Leaf area, Leaf number, Plant height and dry matter weight of the crops were assessed. On the Plant height and Leaf number, application of 75:25 CMC/SA combination resulted in taller plants and more leafiness at 3 WAP compared to 75:25 CMC/CSD combination. The application of 100kgN/ha as sole Sulphate of Ammonia, gave the least leaf number and the shortest plant at 4WAP. The sole application of any of the organic fertilizers 100kgN/ha has proven to be superior in terms of (vegetative yield) of Telfairia occidentalis (ugu-elu) than its combination of each of the organic fertilizer with sulphate of ammonia.Keywords: Organic fertilizer, Inorganic fertilizer, Fluted pumpkin, Yield.